2017
DOI: 10.1080/13102818.2017.1326013
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ghrelin-positive mast cells in rat stomach

Abstract: It is known that the gastrointestinal peptide hormone ghrelin is expressed in human and rodent B lymphocytes, T lymphocytes, monocytes and natural killer cells. However, there are no data about ghrelin expression by mast cells. These facts, as well as the common progenitor cells of mast cells and the above-mentioned immune cells, motivated us to undertake the current work in order to prove that like other granulocytes, rat gastric mast cells are capable of immunohistochemical expression of ghrelin. Gastric wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Ninety-seven percent (97%) of these cells were observed in alveolar septa and 3% in vascular walls, but no metachromatic cells were found within the alveoli. In the current study we used anti-tryptase antibody to identify mast cells which express GHR as we did in our previous study in rat stomach [8]. It is known that Try plays a key role in allergic diseases by amplifying the responses of mast cells to diff erent stimuli including allergens [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety-seven percent (97%) of these cells were observed in alveolar septa and 3% in vascular walls, but no metachromatic cells were found within the alveoli. In the current study we used anti-tryptase antibody to identify mast cells which express GHR as we did in our previous study in rat stomach [8]. It is known that Try plays a key role in allergic diseases by amplifying the responses of mast cells to diff erent stimuli including allergens [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin immunoreactivity in MCs was established in the serosal, muscular, submucosal and mucosal layers of the rat stomach [8]. Thus, the authors suggested that these cells are probably an important source of GHR with a variety of physiological functions, such as regulation of stomach epithelial, glandular and muscular functions.…”
mentioning
confidence: 99%